2022
DOI: 10.3758/s13421-022-01346-7
|View full text |Cite
|
Sign up to set email alerts
|

Does ROC asymmetry reverse when detecting new stimuli? Reinvestigating whether the retrievability of mnemonic information is task-dependent

Abstract: Recently, it has been suggested that the mnemonic information that underlies recognition decisions changes when participants are asked to indicate whether a test stimulus is new rather than old (Brainerd et al., 2021, Journal of Experimental Psychology: Learning Memory, and Cognition, advance online publication). However, some observations that have been interpreted as evidence for this assertion need not be due to mnemonic changes, but may instead be the result of conservative response strategies if the possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 48 publications
2
14
2
Order By: Relevance
“…In other words, the same result could have been observed according to SDT models exhibiting symmetric ROCs if mnemonic sensitivity was affected by the status of the target being probed; that is, if memory performance was somehow impaired in the m*-alternative forced-choice identification task compared to the m-alternative forced-choice identification task. But as mentioned above, that is exactly what our earlier results suggested (Meyer-Grant & Klauer, 2022b). We therefore concluded that "our finding [...] removes the experimentumcrucis status from Experiment 3 in Kellen et al (2021)" (Meyer-Grant & Klauer, 2022b) and that "there is still no clear [emphasis added] evidence for ROC asymmetry that does not rely on either confidence ratings or bias manipulations" (Meyer-Grant & Klauer, 2022b, p. 13).…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…In other words, the same result could have been observed according to SDT models exhibiting symmetric ROCs if mnemonic sensitivity was affected by the status of the target being probed; that is, if memory performance was somehow impaired in the m*-alternative forced-choice identification task compared to the m-alternative forced-choice identification task. But as mentioned above, that is exactly what our earlier results suggested (Meyer-Grant & Klauer, 2022b). We therefore concluded that "our finding [...] removes the experimentumcrucis status from Experiment 3 in Kellen et al (2021)" (Meyer-Grant & Klauer, 2022b) and that "there is still no clear [emphasis added] evidence for ROC asymmetry that does not rely on either confidence ratings or bias manipulations" (Meyer-Grant & Klauer, 2022b, p. 13).…”
Section: Introductionsupporting
confidence: 59%
“…But as mentioned above, that is exactly what our earlier results suggested (Meyer-Grant & Klauer, 2022b). We therefore concluded that "our finding [...] removes the experimentumcrucis status from Experiment 3 in Kellen et al (2021)" (Meyer-Grant & Klauer, 2022b) and that "there is still no clear [emphasis added] evidence for ROC asymmetry that does not rely on either confidence ratings or bias manipulations" (Meyer-Grant & Klauer, 2022b, p. 13). However, Kellen and Singmann (2022) find fault with both of these statements and argue that they are unsubstantiated.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…These findings have led to the proposition of the ’constancy-of-slopes’ generalization (Ratcliff et al, 1994 ). Although this generalization was later overturned by work showing that the ROC asymmetry can vary depending on task parameters or conditions (e.g., Heathcote , 2003 ; Meyer-Grant & Klauer, 2023 ; Dobbins , 2023 ; Hintzman , 2004 ), most of these manipulations failed to produce estimates of lure variability that exceed target variability.…”
mentioning
confidence: 99%